Profit Improvement and Industrial Marketing through Financial Insights Empowerment and Website Design - Murni, Sri; Seventi P, Ignatia Sri; Octaria, Dini; Rahmawati, Rahmawati (Faculty of Economics Universitas Negeri Yogyakarta in collaboration with the Institute for, 2016)
Abstract: Profit Improvement and Industrial Marketing through Financial Insights Empowerment and Website Design. The purpose of this study is to increase profitability and marketing of “atsiri” oil industries in Wonogiri through the empowerment of financial insight and website design. This research was a cross sectional study. The subjects of this study are CV Putra and CV Sekar Melati which are small medium industry producing “atsiri” oil in Girimarto Wonogiri. Data was collected through three stages, namely a preliminary study, design, development and validation of models. The results showed that the empowerment of financial insight and design of the website has improved profit and marketing of “atsiri” oil industries in Wonogiri.Keywords: Financial Insights, website design, Marketing, ProfitAbstrak: Peningkatan Profit dan Pemasaran Industri melalui Pemberdayaan Wawasan Keuangan dan Perancangan Website. Tujuan penelitian ini adalah untuk meningkatkan profit dan pemasaran industri minyak atsiri di Wonogiri melalui pemberdayaan wawasan keuangan dan rancangan website. Penelitian ini merupakan penelitian cross sectional dengan subjek penelitian IKM CV Giri Putra dan CV Sekar Melati yang merupakan IKM penghasil minyak atsiri di Kecamatan Girimarto Kabupaten Wonogiri. Teknik pengumpulan data dilakukan melalui tiga tahapan yaitu studi pendahuluan, pengembangan desain, dan validasi model. Hasil penelitian menunjukkan bahwa pemberdayaan wawasan keuangan dan rancangan website terbukti telah meningkatkan profit dan pemasaran industri minyak atsiri di Wonogiri.Kata kunci: Wawasan keuangan, Rancangan website, Pemasaran, Profit